Security technology for data transmission to the internet of things devices under the application of blockchain technology. (15th May 2023) - Zhou, Guangping
The objectives of this work are to improve the security of citizen identity verification, and data privacy in the network environment, to solve the problems of low security in the process of network information transmission when privacy cannot be reasonably maintained. It aims to further optimise the environment for network information transmission, improve the security and concealment in the process of information transmission and enhance the expansion and application of blockchain technology in the field of network security, thus providing a strong technical guarantee for information transmission, making it safer and more reliable in practice. An authentication transmission system for general data of the Internet of Things (IoT) based on the application of blockchain technology is proposed. In this process, the Gossip consensus algorithm is innovatively integrated into the data transmission process.